2009
DOI: 10.1017/s0007114508143586
|View full text |Cite
|
Sign up to set email alerts
|

Fruit, vegetable and bean intake and mortality from cardiovascular disease among Japanese men and women: the JACC Study

Abstract: To examine the association of plant-based food intakes with CVD and total mortality among Japanese. In the Japan Collaborative Cohort Study for Evaluation of Cancer Risk, 25 206 men and 34 279 women aged 40-79 years, whose fruit, vegetable and bean intakes were assessed by questionnaire at baseline in 1988 -90, were followed for 13 years. Deaths from total stroke, stroke subtypes, CHD and total CVD, according to the International Classification for Diseases 10th Revision, were registered. During 756 054 person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
138
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(145 citation statements)
references
References 25 publications
5
138
0
2
Order By: Relevance
“…Individual prospective cohort studies published since the meta-analyses (18)(19)(20)(21) have tended to confirm the association (22)(23)(24)(25)(26)(27)(28) , although these studies do vary in terms of the dietary assessment and statistical analysis methodology used. Within these later studies there has also been some inconsistency in terms of whether it is total FV intake that is associated with reduced CHD risk, or fruit or vegetables alone (22)(23)(24) or specific classes of FV (26) .…”
Section: Ecological/modelling Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual prospective cohort studies published since the meta-analyses (18)(19)(20)(21) have tended to confirm the association (22)(23)(24)(25)(26)(27)(28) , although these studies do vary in terms of the dietary assessment and statistical analysis methodology used. Within these later studies there has also been some inconsistency in terms of whether it is total FV intake that is associated with reduced CHD risk, or fruit or vegetables alone (22)(23)(24) or specific classes of FV (26) .…”
Section: Ecological/modelling Studiesmentioning
confidence: 99%
“…Within these later studies there has also been some inconsistency in terms of whether it is total FV intake that is associated with reduced CHD risk, or fruit or vegetables alone (22)(23)(24) or specific classes of FV (26) . It is also unclear whether the association is equally strong in both genders (22) , or is stronger in a particular subset of the population studied, for example, smokers (27) .…”
Section: Ecological/modelling Studiesmentioning
confidence: 99%
“…Among the thirty-four articles obtained after screening on the basis of title and abstract, twenty studies were excluded after a full-text examination because they were not relevant for the research (n 11), did not study CVD as outcome (n 3), had a study design other than prospective (n 2), reported insufficient statistics (n 2), were conducted on the same cohort of another study but had shorter follow-up (n 1) or considered composite legume and other foods consumption (n 1). This inclusion strategy resulted in the final inclusion of fourteen studies (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and thirty-two data sets eligible to be considered for the quantitative analysis. Studies included were conducted on eleven cohorts and accounted for a total of 367 000 individuals and 18 475 cases of CVD, including 7451 CHD and 6336 stroke cases.…”
mentioning
confidence: 99%
“…However, the association was not significant when analyses included men only, when studies were conducted in non-Mediterranean countries and after controlling for dietary variables (Table 2). A second analysis was conducted including only studies that specifically considered CVD as the outcome (17,19,22,24,30) . Overall, a decreased risk of 10 % (RR = 0·90; 95 % CI 0·84, 0·97; Fig.…”
mentioning
confidence: 99%
“…Epidemiological data support consumption of fruits and vegetables in the reduction of cardiovascular risk (1)(2)(3)(4)(5) leading to supportive recommendations by the World Health Organisation (6), European Society of Cardiology (7) and jointly the American College of Cardiology and American Heart Association (8). Many components may contribute to benefits including potassium, non-starch polysaccarides, carotenoids, vitamin C and E and phenolic compounds with bioactive phytochemical constituents having a C 6 -C 3 -C 6 flavonoid structure.…”
Section: Introductionmentioning
confidence: 99%